2022
DOI: 10.1210/endocr/bqac020
|View full text |Cite|
|
Sign up to set email alerts
|

Cross-ancestry Genome-wide Association Studies of Sex Hormone Concentrations in Pre- and Postmenopausal Women

Abstract: Objective Concentrations of circulating sex hormones have been associated with a variety of diseases in women and are strongly influenced by menopausal status. We investigated the genetic architectures of circulating concentrations of estradiol, testosterone, and sex hormone binding globulin (SHBG) by menopausal status in women of European and African ancestry. Methods Using data on 229,966 women from UK Biobank, we conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…The gonadal phenotypes from XY mutant mice range from ovotestes to ovaries, thus mimicking those found in human patients carrying coding mutations on FGF9 43 , or in FGFR2 that encodes its gonadal receptor 63 . Remarkably, this novel regulatory region also contains several human GWAS hits associated with fluctuations in testosterone levels [44][45][46] , a phenotype that is consistent with altered FGF9 regulation. Overall, METALoci revealed important insights into the process of sex determination, going from fundamental mechanisms of gene regulation to their relevance in vivo.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The gonadal phenotypes from XY mutant mice range from ovotestes to ovaries, thus mimicking those found in human patients carrying coding mutations on FGF9 43 , or in FGFR2 that encodes its gonadal receptor 63 . Remarkably, this novel regulatory region also contains several human GWAS hits associated with fluctuations in testosterone levels [44][45][46] , a phenotype that is consistent with altered FGF9 regulation. Overall, METALoci revealed important insights into the process of sex determination, going from fundamental mechanisms of gene regulation to their relevance in vivo.…”
Section: Discussionmentioning
confidence: 70%
“…Specifically, we identified a noncoding region located approximately 250 Kb downstream of Fgf9, whose deletion was predicted to be disruptive of its HH metaloci. Interestingly, the human homologous region contains GWAS hits associated with abnormal testosterone levels [44][45][46] , a phenotype that is consistent with alterations in FGF9 expression (Extended Data Table 2). To validate the METALoci predictions, we generated a 306 Kb homozygous deletion (Δ306) within the 1.15 Mb TAD of Fgf9, in mouse embryonic stem cells (mESC).…”
Section: Metaloci Simulations Reveal a Novel Non-coding Region Downst...mentioning
confidence: 92%
“…Finally, we evaluated whether the 27 novel genome-wide significant loci, uniquely identified by T SG Q but missed by T SG F , T SG M and T SG L in the UK Biobank data, are biologically relevant to the testosterone level phenotype. According to the GWAS catalog (Buniello et al, 2018), nine out of the 27 loci were previously reported to be associated with either testosterone level or steroid biosynthesis pathway where testosterone is synthesized (Haas et al (2022); Ruth et al (2020); Richardson et al (2022);Hoffmann et al (2018)). Furthermore, we used Ensembl Variant Effect Predictor (McLaren et al, 2016) to extract a list of genes affected by the top SNPs in these loci, of which multiple genes were previously reported to be associated with testosterone or the cholesterol level (Table 1).…”
Section: Sex-stratified Vs Sex-combinedmentioning
confidence: 99%
“…Finally, we evaluated whether the 27 novel genome-wide significant loci, uniquely identified by TSG Q but missed by TSG F , TSG M and TSG L in the UK Biobank data, are biologically relevant to the testosterone level phenotype. According to the GWAS catalog (Buniello et al, 2018), nine out of the 27 loci were previously reported to be associated with either testosterone level or steroid biosynthesis pathway where testosterone is synthesized (Haas et al (2022); Ruth et al (2020);Richardson et al (2022);Hoffmann et al (2018)). Furthermore, we used Ensembl Variant Effect Predictor (McLaren et al, 2016) to extract a list of genes affected by the top SNPs in these loci, of which multiple genes were previously reported to be associated with testosterone or the cholesterol level (Table 1).…”
Section: Application To Gwas Of the Testosterone Levels In The Uk Bio...mentioning
confidence: 99%